Implementasi Program Kelas Akselerasi di Madrasah Aliyah Negeri 3 Palembang - Devy Nursanty; Bukman Lian; Nila Kesumawati (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to describe the implementation of the accelerated class program, find out the supporting factors, inhibiting factors and how to overcome the obstacles in implementing the accelerated class program in improving the quality of graduates at MAN 3 Palembang. Research using descriptive method with a qualitative approach. Data collection techniques through observation, interviews and documentation. The objects of research were representatives of the curriculum sector, class program coordinators, teachers and students of MAN 3 Palembang. Data were analyzed by means of data collection, data reduction, data presentation and conclusions. Research result ; The implementation of the accelerated class program has gone well; Supporting factors are support from the government, community, parents, adequate facilities and infrastructure, as well as a conducive madrasah environment; The constraining factor is the heavier learning load; Ways to overcome obstacles are counseling guidance, better learning facilities, teachers using a variety of learning methods, and holding outbound programs every grade increase. The quality of graduates is that all students pass one hundred percent and are accepted at state universities and official schools. In conclusion, the implementation of the accelerated class program at MAN 3 Palembang has gone well. Keywords: Acceleration, Implementation, and quality of graduates